COX-2 in cancer: Gordian knot or Achilles heel? - Stasinopoulos, Ioannis; Shah, Tariq; Penet, Marie-France; Krishnamachary, Balaji; Bhujwalla, Zaver M. (Frontiers in Pharmacology, 2013)
The networks of blood and lymphatic vessels and of the extracellular matrix and their cellular and structural components, that are collectively termed the tumor microenvironment, are frequently co-opted and shaped by cancer cells to survive, invade and form distant metastasis. With an enviable capacity to adapt to continually changing environments, cancer represents the epitome of functional chaos, a stark contrast to the hierarchical and organized differentiation processes that dictate the development and life of biological organisms. The consequences of changing landscapes such as hypoxia and acidic extracellular pH in and around tumors create a cascade of, or themselves are results of, changes in multiple pathways and networks that become apparent only several years later as recurrence and metastasis. These molecular and phenotypic changes approach the complexities of a ‘Gordian Knot’. We review evidence from our studies and from literature suggesting that COX-2 biology presents a nodal point in cancer biology and an ‘Achilles heel’ of COX-2-dependent tumors.